Synthesis, characterization and thermochemistry of synthetic Pb-AS, Pb-Cu and Pb-Zn jarosites - Forray, F.; Smith, A.; Navrotsky, A.; Wright, Kathleen; Hudson-Edwards, K.; Dubbin, William (Pergamon, 2014)
The enthalpy of formation from the elements of well characterized Pb–As, Pb–Cu, and Pb–Zn synthetic jarosites, corresponding to chemical formulas (H3O)0.68±0.03Pb0.32±0.002Fe2.86±0.14(SO4)1.69±0.08(AsO4)0.31±0.02(OH)5.59±0.28(H2O)0.41±0.02,(H3O)0.67±0.03Pb0.33±0.02Fe2.71±0.14Cu0.25±0.01(SO4)2±0.00(OH)5.96±0.30(H2O)0.04±0.002 and (H3O)0.57±0.03Pb0.43±0.02Fe2.70±0.14Zn0.21±0.01(SO4)2±0.00(OH)5.95±0.30(H2O)0.05±0.002, was measured by high temperature oxide melt solution calorimetry and gave DHf = 3691.2 ± 8.6 kJ/mol, DHf = 3653.6 ± 8.2 kJ/mol, and DHf = 3669.4 ± 8.4 kJ/mol, respectively. Using estimated entropies, the standard Gibbs free energy of formation from elements at 298 K DGf of the three compounds were calculated to be 3164.8 ± 9.1, 3131.4 ± 8.7, and 3153.6 ± 8.9 kJ/mol, respectively. Based on these free energies, their log Ksp values are 13.94 ± 1.89, 4.38 ± 1.81 and 3.75 ± 1.80, respectively. For this compounds, a log10 {Pb2+}–pH diagram is presented. The diagram shows that the formation of Pb–As jarosite may decrease aqueous arsenic and lead concentrations to meet drinking water standards. The new thermodynamic data confirm that transformation of Pb–As jarosite to plumbojarosite is thermodynamically possible.